The Impact of Homophily and Herd Size on Decision Confidence in the E-commerce Context: A Social Identity Approach - Munawar, Mariam (My University, 2021)
As online shopping continues to grow rapidly, research indicates its massive uptake can be the result of the integration of social media technologies within the e-commerce interface. This has been further exacerbated by the COVID-19 pandemic which has led to an acceleration in the use of e-commerce. However, despite the growing popularity of e-commerce, shopping online is characterized by high levels of uncertainty given the spatial and temporal separation between consumer and vendor. This presents a dire impact on a consumer’s decision-making process and can specifically impact a consumer’s decision confidence. Decision confidence is an important construct that has been shown to be central in influencing a consumer’s behaviour, specifically in regards to purchase-related activities. Few studies have shed light on the factors influencing a consumer’s decision confidence in the e-commerce context. Online shopping platforms fitted with social data markers are able to gauge and track the activities and attributes of online consumers, providing convenient heuristics on various measures such as the total number of recommendations for a product, or the degree of similarity between consumers. These markers may facilitate group identification through the development of herd behaviour. Herd behaviour arises in situations of uncertainty and motivates individuals to identify with a group (herd), and conform to its actions. Various aspects of a herd can influence group identification. This research focuses on two aspects of herd behaviour in e-commerce environments: homophily and herd size. Homophily is the degree to which individuals are similar, and in this study, we examine homophily from the perspective of an individual and the herd to which they may be exposed to. Herd size is the number of individuals in a group taking a specific action such as an online purchase decision. Drawing on the social identity approach and uncertainty identity theory, this investigation hones in on how homophily and herd size arise in the e-commerce context, and examines how group identification through homophily and herd size may reduce uncertainty and build decision confidence through the formation of trust, entitativity, sense of community and information helpfulness. A research model is developed along with a set of supported hypotheses. An online experiment utilizing a hypothetical e-commerce website was conducted with 400 participants. The results were analyzed using structural equation modeling and choice-based conjoint analysis. The results suggest that while homophily significantly impacts trust, sense of community, entitativity and information helpfulness, herd size does not. The results also suggest that whereas trust, sense of community and information helpfulness positively impact decision confidence, entitativity does not. It was also empirically demonstrated that participants preferred measures of homophily in the e-commerce interface more than measures of herd size. Furthermore, it was demonstrated that participants preferred measures indicating homophily in interests and demographics more than information on either alone, and that information on homophily in interests was more preferred than information on homophily in demographics.
Keywords: E-COMMERCE; HERD SIZE; HOMOPHILY; UNCERTAINTY; DECISION CONFIDENCE